Pengaruh Konten Marketing dan Diskon Terhadap Keputusan Pembelian Melalui Kepercayaan Konsumen - Putri Cahya, Ananda Pratama; Suyono, Suyono (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study discusses the effect of content marketing and discounts on consumer decisions through consumer trust as a mediating variable for students who use Aerostreet shoes in the East Java region. Using a type of quantitative research with the aim of knowing whether content marketing and discounts affect purchasing decisions through consumer trust as a mediating variable. The respondents in this study were students who use Aerostreet shoes in the East Java region, totaling 97 respondents. The data collection technique was carried out by distributing questionnaires through the Google form online and then the questionnaires were processed using the help of a Partial Least Square (PLS) data analysis measuring tool. In proving and analyzing this, valid and reliable questionnaires were tested (Outer Model) and structural model testing was carried out in the hypothesis testing section (Inner Mode I). Based on the results of this study (1) Content Marketing has no significant effect on purchasing decisions (2) Content Marketing has a significant effect on consumer confidence (3) Discounts have a significant effect on purchasing decisions (4) Discounts have a significant effect on consumer confidence ( 5) Consumer trust has a significant effect on purchasing decisions (6) Content Marketing through consumer trust has a significant effect on purchasing decisions (7) Discounts through consumer trust have a significant effect on purchasing decisions